Independensi Komisi Pemberantasan Korupsi Pasca Undang-Undang Nomor 19 Tahun 2019 - Mohammad Mahrus Ali; Zaka Firma Aditya; Abdul Basid Fuadi (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
Since its establishment, the Corruption Eradication Commission (Komisi Pemberantasan Korupsi-KPK) has been designed as a state independent agency. The purpose of granting independence to the KPK is to guard against influence by any power. The second revision of the KPK Law through Law Number 19 of 2019 contains fundamental changes to the KPK institution, namely: the establishment of the Supervisory Board, the placement of the KPK in the executive branch, employment status, and examiner or investigator status. The revision not only limits the authority of the KPK but also creates an impact on the independence of the KPK. The principles of independence of the KPK, as typical of state independent agencies and anti-corruption agencies have faded through the regulation of Law Number 19 of 2019. The implication is that the KPK has an increasingly limited latitude and is not independent of the influence of other powers, particularly the executive. Without repositioning the KPK institution, the agenda for eradicating corruption will become gradually uncertain. Without restoring its independence, the existence of the KPK is increasingly losing relevance, because the President is actually in the lead of two other corruption eradication law enforcement agencies, namely the police and the prosecutor’s office.